Analisis Yuridis Normatif terhadap Pertimbangan Hakim dalam Penyelesaian Sengketa Perdata - Arci Agwan; Dinda Cahyanih; Hilda Nurlisa; Prayoga Gustiawan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze judicial considerations in the settlement of civil disputes through a normative juridical approach. The focus of the research is directed toward examining how judges assess legal facts and evidence and relate them to applicable legal norms in civil court decisions. This research employs a statutory approach and a case approach, using primary legal materials such as legislation and court decisions, as well as secondary legal materials including legal literature and academic journals. The findings indicate that judicial considerations play a central role in determining the quality of civil judgments. Well-structured and reasoned considerations contribute to legal certainty and a sense of justice for the parties, whereas insufficient reasoning may lead to legal uncertainty. Therefore, strengthening the quality of judicial considerations is essential to enhance the effectiveness of civil dispute resolution through judicial mechanisms.